Multiwavelength study of OT 081: broadband modelling of a transitional blazar - Abe, Hyuga; Ait Benkhali, Faical; Quirrenbach, Andreas; Wagner, Stefan; Marx, Ramin (Monthly notices of the Royal Astronomical Society, 2025)
OT 081 is a well-known, luminous blazar that is remarkably variable in many energy bands. We present the first broadband study of the source, which includes very high energy (VHE, E > 100 GeV) γ-ray data taken by the MAGIC (Major Atmospheric Gamma-ray Imaging Cherenkov telescopes) and H.E.S.S. (High Energy Stereoscopic System) imaging Cherenkov telescopes. The disco v ery of VHE γ-ray emission happened during a high state of γ-ray activity in July 2016, observed by many instruments from radio to VHE γ-rays. We identify four states of activity of the source, one of which includes VHE γ-ray emission. Variability in the VHE domain is found on daily time-scales. The intrinsic VHE spectrum can be described by a power law with index 3 . 27 ±0 . 44 stat ±0 . 15 sys (MAGIC) and 3 . 39 ±0 . 58 stat ±0 . 64 sys (H.E.S.S.) in the energy range of 55–300 and 120–500 GeV, respectively. The broadband emission cannot be successfully reproduced by a simple one-zone synchrotron self-Compton model. Instead, an additional external Compton component is required. We test a lepto-hadronic model that reproduces the data set well and a proton-synchrotron-dominated model that requires an extreme proton luminosity. Emission models that are able to successfully represent the data place the emitting region well outside of the broad-line region to a location at which the radiative environment is dominated by the infrared thermal radiation field of the dusty torus. In the scenario described by this flaring activity, the source appears to be a flat spectrum radio quasar (FSRQ), in contrast with past categorizations. This suggests that the source can be considered to be a transitional blazar, intermediate between BL Lac and FSRQ objects.